The Ambivalence of Sexual Orientation in H. G. Wells’ The First Men in the Moon - Rifki Dermawan (English Department, Faculty of Humanities, Andalas University, 2015)
The article reveals the ambivalence of human’s sexual orientation reflected in science fiction novel The First Men in the Moon by Herbert George Wells. Focus of the research is to look at the contradiction in Mr. Bedford’s sexual orientation, the main character and narrator, from the perspective of psychoanalysis. The research applies the psychoanalysis theory of Sigmund Freud encompassing the concepts of Id, Ego and Superego, dream symbolism and sexual imagery. The methods of research consist of three stages; collecting the data, analyzing the data and presenting the result of analysis descriptively. The result of analysis indicates the ambivalence in Mr. Bedford’s sexual orientation. Besides, the writer proves that the ambivalence in Mr. Bedford’s sexual orientation leads to the character’s hesitation in giving important decision regarding his future.Keywords: ambivalence, psychoanalysis, sexual orientation, character